2018
DOI: 10.1021/acsami.8b08959
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Inert h-BN/Bilayer Graphene Interface in All-Two-Dimensional Heterostructure Field Effect Transistors

Abstract: Bilayer graphene field effect transistors (BLG-FETs), unlike conventional semiconductors, are greatly sensitive to potential fluctuations because of the charged impurities in high- k gate stacks because the potential difference between two layers induced by the external perpendicular electrical filed is the physical origin behind the band gap opening. The assembly of BLG with layered h-BN insulators into a van der Waals heterostructure has been widely recognized to achieve the superior electrical transport pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…Because the channel resistance reached ~5 G, Ioff has already reached the measurement limitation. Therefore, it is not meaningless to discuss Ion/Ioff, but it reaches ~510 5 [16]. Moreover, for Cgc in all 2D hetero, it is demonstrated that the electron trap/detrap response at this heterointerface is suppressed to an undetectable level in the measurement frequency range between 1 kHz and 2 MHz.…”
Section: All 2d Heterostructure Blg Fetmentioning
confidence: 93%
“…Because the channel resistance reached ~5 G, Ioff has already reached the measurement limitation. Therefore, it is not meaningless to discuss Ion/Ioff, but it reaches ~510 5 [16]. Moreover, for Cgc in all 2D hetero, it is demonstrated that the electron trap/detrap response at this heterointerface is suppressed to an undetectable level in the measurement frequency range between 1 kHz and 2 MHz.…”
Section: All 2d Heterostructure Blg Fetmentioning
confidence: 93%
“…Moreover, the CVD growth of BNNTs around CNTs requires air-suspended CNTs and substrates that withstand high temperatures. Once uniform BN layers are formed, insulating properties of h-BN (Figure 9h) [3] that depend on its layer number should be controlled by selective etching of BNNT layers over CNTs [155,156] or other approaches for the use in electronic devices, where a good electrical contact to CNTs is necessary.…”
Section: Heterostructures Of Carbon Nanotubes Coated By Hexagonal Boron Nitridementioning
confidence: 99%
“…[12][13][14][15] The magnitude of the band gap can be controlled by the intensity of the applied electric field, with reported experimental values up to 250 meV. 14,15 Because this overcomes some of the limitations of gap-less single layer graphene (SLG), the synthesis of AB-BLG is important for the fabrication of functional graphene-based semiconductor devices, such as field-effect transistors (FETs), 16 spintronic 17 and optoelectronic devices. 18 However, since even small twist angles of 0.1°modify the band structure of AB-BLG and prevents the band gap opening, 1,10,11,19 an almost perfect AB stacking is required for the device operations.…”
Section: Introductionmentioning
confidence: 99%